A Contemporary Evaluation on Posterior Direct Restoration Teaching among Undergraduates in Dental Schools in Malaysia - Muhammad Syafiq Alauddin; Norazlina Mohammad; Azlan Jaafar; Faizah Abdul Fatah; Aimi Amalina Ahmad (MDPI AG, 2021)
There is a current trend to restore posterior teeth with composite resin due to increasing demands on natural tooth colour restoration and increased concern about the safety of amalgam restorations. The objective was to evaluate the current teaching of posterior direct restoration among restorative dental lecturers in Malaysia compared to available international literature. An online questionnaire, which sought information on the teaching of posterior restoration was developed and distributed to 13 dental schools in Malaysia. The response rate for the questionnaire was 53.8%. The most popular posterior restoration teaching methods among the respondents were lecture (95.7%), demonstration (87.0%) and problem-based learning (PBL) (73.9%), while continuous assessment and a practical competency test (82.6%) were the most popular assessment methods. Placing a hard setting calcium hydroxide and GIC base for deep cavity restored by composite restoration was taught in 79.2% of cases. The standard protocols for posterior composite restoration were incremental filling in deep cavity (87.5%), using circumferential metal bands with wooden wedge (91.7%), with a total etch system (95.8%), using a light emitting diode (LED) light curing unit (91.7%), finishing using water cooling (80%) and finishing with a disc (87.5%). Graduates from dental schools in Malaysia received similar theoretical, preclinical and clinical teaching on posterior restoration techniques, although there were variations in the delivery methods, techniques and assessments, pointing to a need for uniformity and consensus.